Growth and yield of bottle gourd (Lagenaria siceraria) as influenced by the trailing method of growing and bio-regulators under semi-arid conditions in Rajasthan - Pooja Devi Meena; O.P. Garhwal (Annals of Agricultural Research, 2024)
A field experiment was conducted at Horticulture Farm, Rajasthan Agricultural Research Institute, Jaipur, during the summer seasons of 2022 and 2023. It consisted of 10 treatment combinations with two growing methods (vertical and horizontal) and five levels of bio-regulators (control, NAA at 200 ppm, GA3 at 150 ppm, ethrel at 200 ppm, and salicylic acid at 150 ppm) in a factorial randomised block design with three replications. The results revealed that the vertical trailing system registered significantly higher vine length (70.12 cm), number of nodes (25.86), number of leaves (24.73), leaf area (518.18 cm2), fruit length (17.70 cm), number of fruits/vine (4.08), average fruit weight (0.78 kg), and fruit yield/vine (3.19 kg) at 45 DAS. Similarly, foliar application of GA3 at 50 ppm registered maximum vine length (67.83 cm), number of nodes (25.76), number of leaves (24.30), leaf area (523.14 cm2), fruit length (17.92 cm), number of fruits/vine (4.13), average fruit weight (0.77 kg), and fruit yield/vine (3.16 kg) as compared to control.